PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. BANK BUKOPIN CABANG S PARMAN - Isrial, Isrial; Iqbal, Muhammad (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2018)
A few factors that cause work satisfaction increased is predicted to have leadership style and work motivation. PT. Bank Bukopin have no optimal proficiency. This research aim to see the influence of leadership style and motivation on employees' work satisfaction. It is a quatitative research using  survey explanatory which it's population is 150 full time worker and contract PT.  Bukopin Bank S. Praman. The sample is chosen using probability technique which is random sampling. Data is analyzed using SPSS version 22 and the metode analysis is double regression linear. Result shows that leadership style and motivation  to employee work satisfaction both influence  significantly to work satisfaction. Partially; variables that influence significantly positive to work satisfaction are leadership style and motivation. Leadership style is the variable that influence work satisfaction the most. It is suggested that leaders must create a harmonious cooperation;  cultivate royalty so that the interaction between sosial and employee as well as employee and boss is better.